2020
DOI: 10.1155/2020/8412468
|View full text |Cite
|
Sign up to set email alerts
|

Panax Notoginseng Saponins Prevent Bone Loss by Promoting Angiogenesis in an Osteoporotic Mouse Model

Abstract: With the aging of the population and the extension of life expectancy, osteoporosis is becoming a global epidemic. Although there are several drugs used to treat osteoporosis in clinical practice, such as parathyroid hormone or bisphosphonates, they all have some serious side effects. Therefore, a safer drug is called for osteoporosis, especially for the prevention in the early stage of the disease, not only the treatment in the later stage. Panax notoginseng saponin (PNS), a traditional Chinese herb, has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…Traditional Chinese medicine (TCM), as an important component of complementary and alternative medicine system, has been used to cure disease in China for over two thousand years ( Tang et al, 2008 ). Several TCM formulas and herbal extracts have been proved to be effective for LBDs by promoting the formation of new bone and improving the quality of calcification ( Hu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), as an important component of complementary and alternative medicine system, has been used to cure disease in China for over two thousand years ( Tang et al, 2008 ). Several TCM formulas and herbal extracts have been proved to be effective for LBDs by promoting the formation of new bone and improving the quality of calcification ( Hu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 23 Several studies had showed that PNS exert anti‐osteoporosis effect in radiation‐induced and ovariectomy‐induced osteoporotic mice by dual action: stimulation of bone formation and inhibition of bone resorption. 24 , 25 Another study found that n‐Butanol extracts of Panax notoginseng, which contained 24.1% ginsenoside Rb1 and 8.4% notoginsenoside R1, inhibited osteoclastogenesis in LPS‐activated RAW264.7 cells by suppressing MAPK signaling pathway. 26 However, whether PNS could play a positive role in IDD remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, human IVDs bear much more mechanical forces than quadrupedal animal due to the upright posture; thus, whether the PNS treatment could work in human require more evidence from bipedal primates animal (eg, rhesus monkey) experiments and clinical trials.PNS is the major component of Xuesaitong, a very widely usedChinese patent medicine, whose mainly pharmacological effect is improving microcirculation. Besides, several studies including our previous study had proved its function in anti-osteoporosis,24,25,35 but no studies have investigated its function in IDD. The present study demonstrated for the first time that appropriate doses of PNS can effectively inhibit EP degeneration and attenuate the decline of IVD volume.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Drynariae Rhizoma (DR), also called Gusuibu in Chinese, has a long history in strengthening bones in clinical use. The biological evaluations reveal that total avonoids of DR have a potent effect on both osteoporotic fracture and large bone defect [13,14]. Fewer studies have investigated the relationship between DR and brain [15,16].…”
Section: Introductionmentioning
confidence: 99%